New reference intervals for endocrinological biomarkers in pediatric patients: what can we learn from the LIFE child study? - Kratzsch Juergen (De Gruyter, 2021)
We established reference intervals for serum concentrations of hormones from healthy pediatric subjects and investigated their associations with gender, body mass index (BMI), puberty and oral contraceptives (oC).